George Frederick Bodley and the Later Gothic Revival in Britain and America - Hall, Michael, 1957- (New Haven : Yale University Press, 2014)
British architect George Frederick Bodley (1827-1907) fundamentally shaped the architecture, art, and design of the Anglican Church throughout England and the world; his work survives in the United States, Australia, India, and Italy, as well as the United Kingdom. This important book is the first to explore the life and work of this major Gothic Revival architect, a man with an evolving outlook on style and aesthetics who believed that every element of a building must be part of an integrated design strategy. A close colleague of William Morris and Edward Burne-Jones, Bodley was the first major patron of Morris's stained glass and, like Morris, was an accomplished textile and wallpaper designer. In 1874 Bodley founded Watts and Company-now celebrating its 140th anniversary-to manufacture ecclesiastical vestments, textiles, and wallpapers. In a seamless blend of architectural, art, and church history, this lavish volume features over 200 illustrations and offers impeccable scholarship on the work of an influential visionary of Victorian design.
Keywords: Bodley, George Frederick, -- 1827-1907.; Church architecture -- Great Britain; Church architecture -- United States; Gothic revival (Architecture) -- Great Britain; Gothic revival (Architecture) -- United States; arkkitehtuuri; gotiikka; kirkkorakennukset; Iso-Britannia; Yhdysvallat